Transcriptomic profiling of nematode parasites surviving vaccine exposure. Issue 5 (April 2018) - Sallé, Guillaume; Laing, Roz; Cotton, James A.; Maitland, Kirsty; Martinelli, Axel; Holroyd, Nancy; Tracey, Alan; Berriman, Matthew; Smith, W. David; Newlands, George F.J.; Hanks, Eve; Devaney, Eileen; et al.
Graphical abstract: Highlights: Surviving Haemonchus contortus from vaccinated sheep were compared with control worms. There is no evidence for changes in expression of genes encoding Barbervax® antigens. There was increased expression of other proteases and regulators of lysosome trafficking. Surviving worms displayed up-regulated lipid storage and defecation abilities. Abstract: Some nematode species are economically important parasites of livestock, while others are important human pathogens causing some of the most important neglected tropical diseases. In both humans and animals, anthelmintic drug administration is the main control strategy, but the emergence of drug-resistant worms has stimulated the development of alternative control approaches. Among these, vaccination is considered to be a sustainable and cost effective strategy. Currently, Barbervax® for the ruminant strongylid Haemonchus contortus is the only registered subunit vaccine for a nematode parasite, although a vaccine for the human hookworm Necator americanus is undergoing clinical trials (HOOKVAC consortium). As both these vaccines comprise a limited number of proteins, there is potential for selection of nematodes with altered sequences or expression of the vaccine antigens. Here we compared the transcriptome of H. contortus populations from sheep vaccinated with Barbervax® with worms from control animals. Barbervax® antigens are native integral membrane proteins isolated from the brush border of the intestinal cells of the adult parasite and many of those are proteases. Our findings provide no evidence for changes in expression of genes encoding Barbervax® antigens in the surviving parasite populations. However, surviving parasites from vaccinated animals showed increased expression of other proteases and regulators of lysosome trafficking, and displayed up-regulated lipid storage and defecation abilities that may have circumvented the effect of the vaccine. Implications for other potential vaccines for human and veterinary nematodes are discussed.